Potencialidades bioeconômicas de espécies frutíferas do município de Tabatinga, Tríplice Fronteira - Amazonas - Marin, Nataniel Gomes (Brasil, 2023)
The Amazon region has the largest number of native agricultural species, especially fruit trees. The extractive production of fruits is an interesting option for the development of the region, adding family labor as a source of income for local populations. Thus, a feasibility study of fruit species in the floodplain and upland areas can contribute significantly to the socioeconomic and environmental development in the border strip between Brazil, Colombia and Peru. The study aimed to analyze the bioeconomic potential of the Amazon nut, the Amazonian tucumã and the Camu-camu in the municipality of Tabatinga-AM, presenting a qualitative approach, involving bibliographical and exploratory research and action research. Through the systematization of information from articles and sites of interest, it was possible to build tables and graphs that allowed understanding the networks and spatial circuits of production and commercialization in the Alto Solimões region. In order to learn about the challenges of production, trade and opportunities for fruit growing at fairs, markets and strategic points of sale in the municipality of Tabatinga, an exploratory survey was carried out, using a semi-structured questionnaire as a data collection instrument, applied with producers/marketing agents present at fairs and markets. The Amazon nut has enormous potential for indigenous peoples and traditional communities, it is considered a species of multiple uses, guaranteeing a source of income for collectors. The commercialization of tucumã is of great economic importance, enabling the Ticuna indigenous people to support themselves as a means of exploitation to complement the family income. The two upland fruits are part of the culture and history of the Ticuna people, where exploration techniques are passed down from father to son. Camu-camu is growing and has great economic potential, putting it on the same level of importance as other traditional fruits, mainly due to its high vitamin C content. of the fruits studied, demonstrating all procedures from collection to commercialization. This study described the potential of fruit growing in the Amazon region and allowed us to understand the dynamics of opportunities and threats of working with seasonal production. However, the strengths of this fruit growing chain will make it possible to understand the importance of products and by-products with added values that can guarantee employment and income and, consequently, quality of life for the people of the region.